1997
DOI: 10.1128/aem.63.4.1633-1636.1997
|View full text |Cite
|
Sign up to set email alerts
|

Genomic classification of fish nodaviruses by molecular phylogenetic analysis of the coat protein gene

Abstract: A molecular phylogenetic analysis of 25 isolates of fish nodaviruses, the causative agents of viral nervous necrosis of marine fish, was performed based on the nucleotide sequences (427 bases) of the coat protein gene. These fish nodaviruses were classified into four clusters: tiger puffer nervous necrosis virus, striped jack nervous necrosis virus, berfin flounder nervous necrosis virus, and red-spotted grouper nervous necrosis virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
221
0
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(251 citation statements)
references
References 8 publications
10
221
0
13
Order By: Relevance
“…Therefore, these results clearly suggest that human cell lines can support the binding of the betanodavirus, possibly by sialic acid, as is the case with fish E-11 cells. Desler et al reported that viral coat protein expression was detected in HeLa cells when these cells were infected with Dicentrarchus labrax encephalitis virus (DlEV) [7], a member of the betanodavirus genus belonging to the RGNNV genotype [15,30]. However, the data presented by Desler et al did not confirm that the human cell line HeLa is susceptible to betanodavirus infection, as their results showed only a limited number of cells which were diffusely stained with antibody against the betanodavirus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, these results clearly suggest that human cell lines can support the binding of the betanodavirus, possibly by sialic acid, as is the case with fish E-11 cells. Desler et al reported that viral coat protein expression was detected in HeLa cells when these cells were infected with Dicentrarchus labrax encephalitis virus (DlEV) [7], a member of the betanodavirus genus belonging to the RGNNV genotype [15,30]. However, the data presented by Desler et al did not confirm that the human cell line HeLa is susceptible to betanodavirus infection, as their results showed only a limited number of cells which were diffusely stained with antibody against the betanodavirus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the RNA2-encoded coat protein controls host specificity. Indeed, a variable region of RNA2, encoding the C-terminal region of the coat protein, is used to divide betanodaviruses into four genotypes [25,29,30]. In addition, the C-terminal sequences of the coat protein are displayed on the surface of the virion [38], suggesting that this region interacts with the cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Betanodaviruses have been classified into four genotypes, designated SJNNV (striped jack nervous necrosis virus), TPNNV (tiger puffer nervous necrosis virus), RGNNV (red grouper nervous necrosis virus) and BFNNV (barfin flounder nervous necrosis virus), using a partial sequence of RNA2, the T4 region, which is a highly variable region of around 400 nt [77,78]. These types exhibit different capabilities for infecting fish species.…”
Section: Betanodaviruses -The Role Of Mutation and Reassortment In Homentioning
confidence: 99%
“…Betanodaviruses have been isolated from more than 30 marine fish species from 14 families and are classified into four genotypes based on a phylogenetic analysis of the coat protein sequences. The genotypes are: striped jack nervous necrosis virus (SJNNV), barfin flounder nervous necrosis virus (BFNNV), tiger puffer nervous necrosis virus (TPNNV) and redspotted grouper nervous necrosis virus (RGNNV) [18,20,21]. Effective control of betanodavirus infection is urgently needed to reduce the significant economic loss caused by the virus in the fish industry.…”
Section: Introductionmentioning
confidence: 99%